2015
DOI: 10.1186/s12885-015-1235-8
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo antiproliferative activity of metformin on stem-like cells isolated from spontaneous canine mammary carcinomas: translational implications for human tumors

Abstract: BackgroundCancer stem cells (CSCs) are considered the cell subpopulation responsible for breast cancer (BC) initiation, growth, and relapse. CSCs are identified as self-renewing and tumor-initiating cells, conferring resistance to chemo- and radio-therapy to several neoplasias. Nowadays, th (about 10mM)e pharmacological targeting of CSCs is considered an ineludible therapeutic goal. The antidiabetic drug metformin was reported to suppress in vitro and in vivo CSC survival in different tumors and, in particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 96 publications
(136 reference statements)
5
38
0
2
Order By: Relevance
“…A number of studies demonstrated the existence of stem cells in canine and human breast cancer cell lines [83][84][85][86][87][88][89]. The study of Dontu and colleagues demonstrated that the stemness of tumor cells is assessed in vitro by their capability to produce mammospheres [90].…”
Section: Effect Of Melatonin In Epithelial Mesenchymal Transition Marmentioning
confidence: 99%
“…A number of studies demonstrated the existence of stem cells in canine and human breast cancer cell lines [83][84][85][86][87][88][89]. The study of Dontu and colleagues demonstrated that the stemness of tumor cells is assessed in vitro by their capability to produce mammospheres [90].…”
Section: Effect Of Melatonin In Epithelial Mesenchymal Transition Marmentioning
confidence: 99%
“…The same cells were resistant to radiation doses of 1–5 Gy and exhibited a reduced loss of colony formation ability. Increased resistance to doxorubicin and no response to paclitaxel treatment were also observed by three other groups [27, 31, 35]. Barbieri et al [31] did not observe any reduction in cell viability, even at the highest concentrations (5–10 µM) of the drugs.…”
Section: Functional Characterization Of Canine Mammary Cancer Stem Cellsmentioning
confidence: 61%
“…Increased resistance to doxorubicin and no response to paclitaxel treatment were also observed by three other groups [27, 31, 35]. Barbieri et al [31] did not observe any reduction in cell viability, even at the highest concentrations (5–10 µM) of the drugs. Discordance between results obtained using cell lines and spheres derived from tumor samples might be explained by possible different gene expressions and cellular properties that occur during the process of immortalization [24].…”
Section: Functional Characterization Of Canine Mammary Cancer Stem Cellsmentioning
confidence: 61%
See 1 more Smart Citation
“…Metformin effects have been evaluated in preclinical studies on different solid tumor models, including breast [89,90], endometrial [91], pancreatic [70], lung [92], prostate [93], head and neck [94] carcinomas, glioma and neuroblastoma [95][96][97], and blood malignancies [98][99][100].…”
Section: Metforminmentioning
confidence: 99%